Development and analysis of wireless heart rate monitoring device - Daud, H. (Institute of Electrical and Electronics Engineers Inc., 2014)
Researchers throughout the years have been searching for methods to improve the available technologies to ease the users worldwide. In medical industries, researchers have made many improvements and development in medical equipment's to ease the medical professionals in serving patients. This work is the continuation of the previous research work in providing complete set of data for analysis on human behavior to set an accurate threshold for device detection. In this work, heart rate is monitored to all age groups for both genders wirelessly from remote locations. Results showed that these various age group is giving average reading that complies to the benchmark reading and is able to provide the necessary threshold value for future device improvement and enhancement. Â© 2014 IEEE.